Kajian Awal terhadap Sistem Pemilihan Somaklon CUi Yang Resistans kepada Colletotrichum capsici (Syd.) Butler & Bisby - Anuar, Nurina; Ahmad, Ismail; Hashim, Azizah (Universiti Putra Malaysia Press, 1994)
Toxin treatment from the anthracnose pathogen, Colletotrichum capsici on chilli tissue culture was utilised as the selection mechanism for variants which are resistant to this pathogen. The crude toxin preparation was sterilised and then added to the MS medium at the concentration of 0, 10, 20, 30 or 40% (v/v). At concentrations higher than 20 %, the toxin prevented the formation of calli from hypocotyl explants, and at 10% and 20 %, the formation of calli was strongly inhibited. The calli which survived the toxin treatment did not regenerate. Conversely, calli which were cultured on MS medium suplemented with VB juice or on the control MS medium, were able to regenerate at 37.6% and 62.7%, respectively. Induction of resistant variants was attempted by inoculating the calli with the konidia from the anthracnose pathogen. The antibiotic which had been extracted from an antagonistic fungus, Chaetomium trilaterale, was added to the MS medium to limit the spread of the pathogen to the medium from the chilli calli. From the antibiotic assay, the developement of the pathogen was dependent on the antibiotic concentration used in the media. The minimum antibiotic concentration which successfully prevented the growth of the fungal pathogen was 100 mg/ml. At that concentration, the fungus was only observed on the calli but not on the medium. However, the calli turned brown after 2 weeks of inoculation. In addition, the calli that survived became compacted and failed to regenerate.